Tracheal Resection in the Management of Thyroid Cancer: An Evidence‐Based Approach. (28th September 2020) - Allen, Meredith; Spillinger, Aviv; Arianpour, Khashayar; Johnson, Jared; Johnson, Andrew P.; Folbe, Adam J.; Hotaling, Jeffrey; Svider, Peter F.
Abstract : Objective: Determine the effect of patient demographics and surgical approach on patient outcomes after tracheal resection in the management of thyroid cancer. Study Design: Systematic review and meta‐analysis. Methods: Systematic review of literature was performed using PubMed, Embase, and Cochrane Library to identify patients with thyroid carcinoma who underwent tracheal resection. Pooled estimates for patient demographics, presenting findings, complications, and outcomes are determined using random‐effects meta‐analyses. Results: Ninety‐six relevant studies encompassing 1, 179 patients met inclusion criteria. Meta‐analysis pooled rates of complications: 1.7% (confidence interval [CI] 0.8–2.5; P < .001; I 2 = 1.85%) airway complications, 2.8% (CI 1.6–3.9; P < .001; I 2 = 13.34%) bilateral recurrent laryngeal nerve paralysis, 2.2% (CI 1.2–3.1; P < .001; I 2 = 6.72%) anastomotic dehiscence. Circumferential resection pooled estimates major complications, locoregional recurrence, distal recurrence, overall survival: 14.1% (CI 8.3–19.9; P < .001; I 2 = 35.26%), 15% (CI 9.6–20.3; P < .001; I 2 = 38.2%), 19.7% (CI 13.7–25.8; P < .001; I 2 = 28.83%), 74.5% (CI 64.4–84.6; P < .001; I 2 = 85.07%). Window resection estimates: 19.8% (CI 6.9–32.8; P < .001; I 2 = 18.83%) major complications, 25.6% (CI 5.1–46.1; P < .014; I 2 = 84.68%) locoregional recurrence, 15.6% (CI 9.7–21.5; P < .001; I 2 = 0%) distal recurrence, 77.1% (CI 58–96.2; P < .001; I 2 = 78.77%) overall survival. Conclusion: Management of invasive thyroid carcinoma may require tracheal resection to achieve locoregional control. Nevertheless, postoperative complications are not insignificant, and therefore this risk cannot be overlooked when counseling patients perioperatively. Laryngoscope, 131:932–946, 2021